Transitivity Analysis in the text of the 1945 Constitution before the Amendment - Bastian Sinaga, Elwyn; Sinar, Silvana; Setia, Eddy (CV. Inara, 2021)
The realization of the text of the 1945 Constitution became the history of the birth of the first constitution in the State of Indonesia. The 1945 Constitution text was then amended four times. The first amendment was in 1999. The second amendment was in 2000. The third amendment was in 2001. The fourth amendment was in 2002. Every amendment occurred in the contents section, but not in the opening section. The 1945 Constitution text is a tool for sharing or describing experiences with others. The meaning of the experience is realized in the text of the 1945 Constitution. There is also the purpose of this research, which is to describe the meaning of experience that is in the text of the 1945 Constitution. This research data is in the form of the 1945 Constitution text which has not been amended because it is fundamental and first. The theory used in this study is the Functional Systemic Linguistics (LSF) theory pioneered by Halliday (2014). Furthermore, to analyze the data using the analysis technique of the model of Miles, Huberman, and Saldana (2014). Based on the results of the study found, namely (1) there are six processes in the text of the 1945 Constitution which are dominated by material processes (2) there are three types of participant, namely participants based on the process, participants based on their numbers, and participants based on their form (3) there are the ten types of circumstant are dominated by circumumstan manner and there is no circumstant extent. It is intended that the text of the 1945 Constitution is generally constructed by a material verb along with a circumstance manner and summary angle, the participants of which are human beings.